LEGAL CHALLENGES FACED BY LOCAL MUSLIM ENTREPRENEURS IN FRANCHISE INDUSTRY - Wong Hua Siong; Nurli Yaacob, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The Malaysian franchise industry continues to achieve healthy growth by contributing RM27 billion to the country’s gross domestic product (‘GDP’) in 2017 while the annual growth rate for 2018 is 9 percent. As of February 2019, 877 current domestic and international franchise brands are registered with the Malaysian authority. Before the enactment of the Franchise Act in 1998, franchising in Malaysia was generally governed by contractual principles. Since the enforcement of the Franchise Act 1998, Malaysia has been promoting the franchise industry extensively via government bodies, especially the Ministry of Domestic Trade and Consumer Affairs. Malaysia does not have a specific framework for Syariah compliant business which is suitable to the local Muslim entrepreneurs, especially in the franchise industry. In fact, Malaysia has vast opportunities in expanding its franchise industry through the amendment of the relevant legal framework. The objective of this article is to look into the legal challenges faced by the local Muslim entrepreneurs in the franchise industry and suggest some proposals on how to make the franchise business and industry Syariah friendly as in some circumstances the franchisors and franchisees are Muslims. This is a qualitative study that involves a systematic study of philosophical and academic views through literature. Therefore, this study is not an empirical study but rather a library study from various primary data sources such as Quran, Hadis, franchising agreement, and secondary data sources namely articles and journals from an online database. The study found that challenges faced by local Muslim entrepreneurs in the franchise industry in Malaysia include the issues of the prohibition against the same business, financial concern, and monopoly by the franchisor. As such, it is suggested that the need for a unique legal framework for Islamic franchising business in Malaysia in order to protect the local Muslim entrepreneurs.